2006
DOI: 10.1002/jnr.20871
|View full text |Cite
|
Sign up to set email alerts
|

Hypoosmolar conditions reduce extracellular volume fraction and enhance epileptiform activity in the CA3 region of the immature rat hippocampus

Abstract: The osmolarity of the extracellular space (ECS) compartment is an important factor determining the excitability of neuronal tissue. In the adult hippocampus an important role of osmolarity and ECS diffusion parameters on the susceptibility to epileptic events is well established, but the influence of hypo- and hyperosmolar conditions on the immature hippocampus remains elusive. To investigate the influence of osmolarity on epileptiform activity, extracellular field potentials were recorded in the CA3 region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 53 publications
4
52
0
Order By: Relevance
“…Several in vitro studies have shown that application of hyperosmolar solutions containing impermeable substances elevates the seizure threshold in rat hippocampus (Traynelis and Dingledine, 1989;Dudek et al, 1990;Pan and Stringer, 1996;Kilb et al, 2006). Hyperosmolar solutions should increase ␣ by shrinking cells, and Traynelis and Dingledine (1989) confirmed this through impedance measurements.…”
Section: Implications Of the Increased Volume Fraction In Aqp4mentioning
confidence: 85%
“…Several in vitro studies have shown that application of hyperosmolar solutions containing impermeable substances elevates the seizure threshold in rat hippocampus (Traynelis and Dingledine, 1989;Dudek et al, 1990;Pan and Stringer, 1996;Kilb et al, 2006). Hyperosmolar solutions should increase ␣ by shrinking cells, and Traynelis and Dingledine (1989) confirmed this through impedance measurements.…”
Section: Implications Of the Increased Volume Fraction In Aqp4mentioning
confidence: 85%
“…Interestingly, at resting state, ECS volume in AQP4 or a-syn knockout mice (AQP4 2/2 or a-syn 2/2 , respectively) is larger than that found in control animals [42,53]. The higher initial value of a was proposed to be a protective mechanism against the fast increase in concentration of neurotoxic substances [54], and thus may contribute to a better outcome in AQP4 swelling, Dmytrenko et al [42] showed that AQP4-mediated water influx plays a role predominantly during pathological states (global ischaemia and strong hypotonic stress) or in states associated with increased potassium concentration, but not during milder stimuli modelling physiological neuronal activity (figure 2).…”
Section: (A) Transient Changesmentioning
confidence: 96%
“…voltage-gated potassium channels; hypotonicity; hypertonicity; TRPV4; intracellular signaling pathway; second messenger system Many studies have shown that osmolarity plays an important role in the regulation of neurons excitability and neurotransmitter release (Andrew et al, 1989;Azouz et al, 1997;Baraban and Schwartzkroin, 1998;Kilb et al, 2006;Saly and Andrew, 1993;Traynelis and Dingledine, 1989). Through this regulation, changes in osmolality can cause many disorders, such as Corresponding author: Lieju Liu Department of Physiology, Tongji Medical College, Huazhong University of Science and Technology, No.…”
Section: Introductionmentioning
confidence: 99%
“…epilepsy (Kilb et al, 2006;Schwartzkroin et al, 1998) in the central nerve system and pain in the peripheral nerve system (Alessandri-Haber et al, 2005;Alessandri-Haber et al, 2004;Alessandri-Haber et al, 2003;Suzuki et al, 2003). Recently, there are evidences that both hypo and hypertonic stimuli can activate C-fiber afferent and induce pain (Alessandri-Haber et al, 2005;Alessandri-Haber et al, 2004;Alessandri-Haber et al, 2003;Suzuki et al, 2003).…”
mentioning
confidence: 99%